Prevalence of inflammatory bowel disease in alcoholic, non-alcoholic and autoimmune pancreatitis: chronisch entzündliche Darmerkrankungen bei Pankreatitis = Prevalence of inflammatory bowel disease in alcoholic, non-alcoholic and autoimmune pancreatitis : inflammatory bowel disease in pancreatitis - Schneider, Alexander; Hirth, Michael; Weiß, Christel; Weidner, Philip; Antoni, Christoph Helmer; Thomann, Anne K.; Reindl, Wolfgang; Ebert, Matthias; Pfützer, Roland (Zeitschrift für Gastroenterologie, 2018)
Objectives Patients with inflammatory bowel disease (IBD) frequently reveal features of pancreatic inflammation. However, the prevalence of IBD in patients with alcoholic pancreatitis (AP) and nonalcoholic pancreatitis (NAP) has not yet been determined, and the prevalence of IBD in patients with autoimmune pancreatitis (AiP) from Germany is unknown.- Aims: Thus, we aimed, first, to determine the prevalence of IBD in AP, NAP, and AiP from a tertiary center in Germany and, second, to characterize patients with AiP and IBD. - Methods We performed a retrospective cross-sectional study to determine the prevalence of IBD in patients with different forms of pancreatitis presenting to our clinic. - Results: Compared to the general population and to a control group with viral hepatitis from our clinic, we observed the most significant increase of IBD in patients with AiP (n = 3/28; p Conclusions Immune-mediated mechanisms related to IBD may participate in the development of AiP, especially AiP type 2, and may also increase the risk for the development of other forms of pancreatic inflammation.